Some regularities of transaction statistics of cryptocurrency Ethereum: opportunities to study the impact of space weather on human economic behavior on a global scale - Vitulyova, Yelizaveta; Moldakhan, Inabat; Grigoriev, Pavel; Suleimenov, Ibragim (Frontiers in Blockchain, 2024)
It is shown that the statistics of transactions of the Ethereum cryptocurrency obeys well-defined patterns. Log dependency ln 𝑁 of the number of users 𝑁 who carried out 𝑛 transactions with the use of Ethereum cryptocurrency during a specific month on ln 𝑛 is a linear one with high accuracy: ln 𝑁 = 𝑏(𝑡) ln 𝑛 + 𝑎(𝑡). Similar statistical patterns are obtained for bitcoin transactions. It has also been established that the behavior of the coefficient 𝑏 appearing in this dependence corresponds with high accuracy to the Bass diffusion model, which describes the dynamics of innovation implementation. It is shown that after the completion of the initial stage of the implementation of the Ethereum and bitcoin cryptocurrencies (since the beginning of 2018), the values of the coefficients a and b are approaching constants. On this basis, a method is proposed for identifying space weather factors on the economic behavior of the human population. In particular, it is shown that the analysis of the cross-correlation between the ratio 𝑎 𝑏 for the Ethereum cryptocurrency and the Ap-index of geomagnetic activity gives an example of additional tools allowing to reveal the influence of space weather factors on the economic behavior of people on a global scale.